Cryoballoon-ablation of atrial fibrillation in patients with heart failure and preserved ejection fraction. (19th May 2022) - Zylla, MM; Leiner, J; Rahm, AK; Hoffmann, T; Lugenbiel, P; Schweizer, P; Scholz, E; Mereles, D; Kronsteiner, D; Kieser, M; Katus, H; Frey, N; et al.
Abstract: Funding Acknowledgements: Type of funding sources: Public Institution(s). Main funding source(s): Deutsches Zentrum für Herz-Kreislauf-Forschung (DZHK) Background: Co-existence of atrial fibrillation (AF) and heart failure with preserved ejection fraction (HFpEF) is common and severely affects morbidity and prognosis. Purpose: This study evaluates outcome after cryoballoon-ablation for AF in HFpEF compared to patients without heart failure employing multiple diagnostic modalities. Methods: A total of 102 patients scheduled for cryoablation of AF with LVEF≥50% were prospectively enrolled. Baseline evaluation included echocardiography, stress echocardiography, six-minute-walk-test, biomarker measurements and quality of life assessment (SF-36). HFpEF was diagnosed according to current guidelines and confirmed applying the HFA-PEFF-Score. Procedural parameters as well as clinical, functional and echocardiographic endpoints at follow-up ≥12 months after AF-ablation were compared between patients with and without HFpEF. Results: Patients with HFpEF (n=24) were older (median: 73.5 years [Q25: 66.5 years; Q75: 75.8 years] vs. 64.5 years [Q25: 55.0 years; Q75: 71.3 years], P<0.001) and more often female (83.3% vs. 28.2%). They were characterized by more pronounced AF-related symptoms (median EHRA-score: 3.0 [Q25:3.0; Q75:3.0] vs. 2.0 [Q25: 2.0; Q75: 3.0], P<0.001), reduced distance in six-minute-walk-test (median 487.5m [Q25: 378.1m; Q75: 517.8m] vs. 539.0m [Q25: 489.3m; Q75:589.1 m], P<0.001), and higher mean left atrial (LA)-pressure measured at the needle tip at transseptal puncture (14.0mmHg [Q25: 10.3mmHg; Q75: 21.5mmHg] vs. 10.0 mmHg [Q25: 8.0mmHg; Q75: 13.3mmHg], P=0.008). Procedural parameters were comparable between the two subgroups. Rates of AF-recurrence, repeat AF-ablation and AF-related re-hospitalization were increased in HFpEF (Figure 1A-C), which was confirmed after adjusting for intergroup differences in sex and age distribution by multiple regression analysis. There was no improvement of heart failure-related symptoms and persistent elevation of cardiac biomarkers, even in HFpEF-patients with successful restoration of sinus rhythm at follow-up (Figure 2A-C). Echocardiographic follow-up showed progression of adverse LA-remodeling (LA-volume index at baseline: 35.8ml/m2 [Q25: 32.2ml/m2; Q75: 41.9ml/m2] vs. 12-month follow-up: 40.5ml/m2 [Q25: 36.0ml/m2; Q75: 51.4ml/m2], P=0.017) and no improvement in diastolic function in HFpEF (E/e' at baseline: 9.7 [Q25: 7.8; Q75: 12.1] vs 12-month follow-up: 10.2 [Q25: 8.4; Q75: 11.8], P=0.874), in particular in patients with HFpEF and AF-recurrence. Quality of life improved in patients without HFpEF in both physical and mental summary scales, however, no beneficial effect was seen in HFpEF. Conclusion: Patients with HFpEF constitute a distinct subgroup with an elevated risk for arrhythmia recurrence after cryoablation of AF. Functional hallmarks and heart-failure related symptoms of HFpEF persisted in our cohort, irrespective of rhythm-status at follow-up. Future research is needed to optimize tailored treatment strategies in HFpEF.